PENGARUH PROGRAM PEMUTIHAN , PEMBEBASAN BEA BALIK NAMA DAN SOSIALISASI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR DI KANTOR SAMSAT KABUPATEN KARANGASEM - Ni Komang Dwi Wiranjani; Sujana, Edy (Vokasi : Jurnal Riset Akuntansi, 2023)
This research aims to determine the effect of whitening programs, transfer of name fees, and tax socialization on taxpayer compliance. This type of research is quantitative research using survey methods. The sampling technique used was accidental sampling with a sample size of 100 respondents. Data collection uses questionnaires. The data analysis technique used in this research is Multiple Linear Regression Analysis using the t test. The data was processed using IBM SPSS Version 26. The results of this study show that the motor vehicle tax fine reduction program has a significant effect on motor vehicle taxpayer compliance, exemption from motor vehicle title transfer fees has a significant effect on motor vehicle taxpayer compliance, and tax socialization has a significant effect on compliance. motor vehicle taxpayers.